VD_FINDINFO Jug / 2024 / 297 vom 23. Januar 2024 - VD Tribunal cantonal (2024)
FRAIS JUDICIAIRES, TORT MORAL, DÉPENS, ASSISTANCE JUDICIAIRE | 49 al. 1 CO, 136 al. 3 CPP (CH), 427 al. 2 CPP (CH), 433 al. 1 let. a CPP (CH)